The making of Syriac Jerusalem: representations of the holy city in Syriac literature of late antiquity and the Middle Ages - Popa, Cătălin-Ştefan ca. 20./21. Jh. (Routledge studies in the early Christian world, 2023)
Foreword -- Introduction -- PART I. The Beginnings of Syriac Christian Pilgrimage to the Holy Land -- PART II. Syriac Christians and the Tradition of the Holy Places of Palestine following the Islamic Conquest of Jerusalem (638-639) -- PART III. The Portrayal of Jerusalem in Syriac Chronicles and Poems on the Second Islamic Conquest and Subsequent Period, and the Presence of Syriac Pilgrims in Palestine in the Late Medieval Period -- Conclusion -- Literature -- Index of Place Names -- Index of Personal Names -- Index of Subjects.